Compositionally graded alloys fabricated using the laser powder bed fusion technique - Wei, Siyuan (Nanyang Technological University, 2023)
Additive manufacturing (AM) has shown advantageous aspects over conventional manufacturing methods, e.g., additional design freedom, ability to fabricate complex shapes without the need for post-processing, and enhanced mechanical performance of the fabricated parts. The development and application of AM techniques, such as laser powder bed fusion (LPBF), however, are hampered by the relatively limited types of alloys that are amenable to AM, e.g., 316L stainless steel, Inconel 718, and Ti64. Therefore, metal AM is still in its nascent stage, with the exploration of new alloy chemistries and/or fabrication of components with unique functional and/or mechanical properties being relatively unexplored. The combination of in-situ alloying and compositionally graded alloy is promising to accelerate the composition screening/alloy designing for AM, as it can rapidly examine the printability, micro-/meso-structure, and properties of the AM-produced parts and therefore shorten the time span between conceptualization of new alloys and their deployment in service. In this study, among the several available AM processes, the LPBF technique is selected to fabricate compositionally graded alloys, as it has higher spatial resolution and lower cost, compared to directed energy deposition (DED) and electron beam powder bed fusion (EBPBF). With three different LPBF setups and four alloy systems examined in this study, the following objectives are achieved: (i) screening out, from a large range of compositions, the alloys that are amenable to LPBF, (ii) examining the effects of the LPBF characteristics, e.g., rapid cooling rate, on the micro-/meso-structure and properties of the fabricated parts with varying chemical compositions, and (iii) evaluating the fabrication methods in terms of types of achieved gradation (stepwise or smooth), efficiency, and level of chemical segregation. Through pre-packing the mixed powders in the powder supply bin, compositionally graded Fe-Al (Al contents in range of 9.8–40.8 at.%), and AlxCrCoFeNi (x = 0.07–0.88 molar ratio) were fabricated and studied. The chemical compositions, microstructures, and mechanical properties were examined to investigate the effect of Al contents. In Fe-Al alloys, the critical Al content for crack-free printing was examined to be 35 at.% and a columnar to equiaxed grain structure transition with increasing Al content is seen along the gradient/building direction, due to the varying levels of constitutional undercooling (CUC). Regarding the AlxCrCoFeNi alloy, the maximum Al that can enable crack-free printing was observed to be x (molar ratio) = 0.5, and the phase variations in the graded alloys were found to be closely associated with x. A CoCrMo-Ni graded alloy (26.8–9.8 wt.% Ni) with smooth compositional gradient was successfully fabricated using a customized LPBF system, where the gradient was created along the transverse direction instead of building direction. Two types of grain morphologies and chemical segregation bands, which are either rich in Ni or in CoCrMo alloy, were observed. Incomplete mixing of the powders combined with the high aspect ratio of the melt pool and the 67° scan rotation between successive layers are the reasons behind the formation of these bands. Detailed mechanical property characterization shows that the microscale chemical segregation can not only strengthen the matrix but also improve the work hardening ability of the bulk material through kinematic hardening mechanism. Compositionally graded Cu-Ni alloys with 0–9.8 wt.% Ni were fabricated using a novel and simple powder supply system in LPBF. With no need to alter the mechanical setup of the LPBF machine or its powder feeding system, this strategy can efficiently create smooth compositional gradient without introducing significant chemical segregations. 7.6 wt.% Ni was proved to be the lower threshold for fabricating nearly full-density Cu-Ni binary alloy. Cu-7.6Ni-3Al (wt.%) was further designed and fabricated. After aging till the peak condition, the Cu-Ni-Al alloy shows significantly higher strength and electrical conductivity than in the as-printed (AP) condition, due to the formation of the Ni3Al precipitates during aging. In this study, three different in-situ alloying methods are utilized on four alloy systems to explore and potential of utilizing compositionally graded alloy as a high-throughput method to study the composition-microstructure-property relationship of the LPBF produced alloys. On the basis of the findings, it is believed that such method can contribute greatly to the alloy designing and further development of AM.